The learning model of Resource-Based learning, Brain-Based learning, and a combination of these two models Resource - Brain-Based learning is believed to be able to improve cognitive, affective, and psychomotor learning outcomes of the Students of SMP Neg - Ravensca Delivia Tehusiarana; Dominggus Rumahlatu (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2023)
The combination of learning in the 21st century related to soft skills is the Resource-Brain Based Learning model which is a combination of Resource-Based Learning and Brain-Based Learning models. They are learning strategies adapted to learning resources and brain work systems that are already naturally programmed to learn. This study aims to see the effect of the Resource-Brain Based Learning model on students' cognitive, affective, and psychomotor thinking learning outcomes on environmental pollution material for class VII in SMP Negeri 20 Central Maluku and SMP Negeri 13 Central Maluku. Research data were analyzed quantitatively using descriptive and inferential statistics in the form of ANCOVA analysis to see the effect of the Resource-Brain Based Learning model on students' cognitive learning outcomes and ANOVA analysis for ANOVA on students' metacognitive outcomes and social attitudes. The results showed that there was an influence of the Resource-Brain Based Learning model on cognitive, affective, and psychomotor learning outcomes.